MENINGKATKAN KOMPETENSI GURU DALAM MENYUSUN ADMINISTRASI PENILAIAN MELALUI SUPERVISI AKADEMIK DI SD INPRES BERU - OLA SISILIA (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
The purpose of this principal's action research is to improve the pedagogical competence of teachers at SD Inpres Beru in compiling assessment administration through academic supervision. This type of research used in this research is school action research. The activities in this study consisted of the stages of action planning, action implementation, observation, and reflection. Data collection techniques used classroom observation techniques. The observation instrument used was a teacher's ability assessment tool (APKG) in the form of learning administration assessment instruments. Analysis of the data used is a comparative descriptive analysis technique. Quantitative data obtained is described in the form of words or explanations. Data comparison is then performed to ensure whether there is an increase in the ability of teachers in the assessment of learning administration. The results showed the findings that academic supervision can improve the ability of teachers in preparing the administration of assessment in learning at SD Inpres Beru by 26.2%.